2009
DOI: 10.1016/j.devcel.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Wnt2/2b and β-Catenin Signaling Are Necessary and Sufficient to Specify Lung Progenitors in the Foregut

Abstract: The primitive foregut is patterned in a manner that spatially promotes proper organ specification along the anterior-posterior foregut axis. However, the molecular pathways that specify foregut endoderm progenitors are poorly understood. We show that Wnt2/2b signaling is required to specify lung endoderm progenitors within the anterior foregut. Embryos lacking Wnt2/2b expression exhibit complete lung agenesis and do not express Nkx2.1, the earliest marker of the lung endoderm. In contrast, other foregut endode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
487
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(528 citation statements)
references
References 39 publications
37
487
4
Order By: Relevance
“…Wnt2 is expressed in the mesenchyme surrounding the epithelial buds and also promotes lung progenitor proliferation. Similar to Wnt7b null animals, Wnt2 null mice have smaller lungs with both epithelial and mesenchymal proliferation defects, but normal overall patterning (Goss et al, 2009). Wnt5a is highly expressed in the distal lung epithelium and surrounding mesenchyme.…”
Section: Epithelial Progenitor Regulationmentioning
confidence: 95%
See 2 more Smart Citations
“…Wnt2 is expressed in the mesenchyme surrounding the epithelial buds and also promotes lung progenitor proliferation. Similar to Wnt7b null animals, Wnt2 null mice have smaller lungs with both epithelial and mesenchymal proliferation defects, but normal overall patterning (Goss et al, 2009). Wnt5a is highly expressed in the distal lung epithelium and surrounding mesenchyme.…”
Section: Epithelial Progenitor Regulationmentioning
confidence: 95%
“…In addition, the molecular regulation of the adult lung progenitors may be different to that of their embryonic counterparts. Wnt signaling is required for embryonic progenitor proliferation Goss et al, 2009). However, specific deletion of b-catenin, which is necessary for canonical Wnt signaling, in a known adult lung progenitor population did not have any effect on airway epithelial growth, maintenance or repair (Zemke et al, 2009).…”
Section: Embryonic and Adult Lung Progenitor Cells: Distinct Lineage-mentioning
confidence: 99%
See 1 more Smart Citation
“…A potential option for the future could be the reactivation of signaling pathways that are active during lung development to induce epithelial repair in the damaged areas similar to the Wnt/β-catenin pathway. 70,105,106 In human lung samples of patients with COPD, a reduction of nuclear β-catenin is detectable. 64 In addition, decreased Wnt/β-catenin activation has been described in different murine models of emphysema and treatment with LiCl attenuated airspace enlargement and prevents the development of emphysema.…”
Section: Role Of Wnt Pathways In Airway Remodelingmentioning
confidence: 99%
“…Experimental evidence has shown that Wnt2/2b and β-catenin signaling are necessary and sufficient to specify lung progenitors in the foregut. 51 The role of the Wnt pathway in thyroid cancer and CSCs has been studied using primary thyroid cancer cells. 7 CSCs isolated from ATCs were most aggressive and tumorigenic compared with CSCs isolated from well differentiated papillary and follicular cancers.…”
mentioning
confidence: 99%